Simulation and performance analysis of a solar-assisted venturi-plasma pasteurization system for milk - Kimia Taki; Bahram Hosseinzadeh Samani (PLoS ONE, 2026)
This research evaluates the feasibility and performance of a novel solar-powered milk pasteurization system integrating a Venturi tube hydrodynamic reactor and liquid-phase cold plasma technology. Designed for a daily capacity of 600 liters, the system utilizes flat-plate collectors and photovoltaic panels to supply thermal and electrical energy, respectively. Performance was simulated across three Iranian cities with distinct climates: Shahrekord (cold, mountainous), Yazd (hot, arid), and Bandar-e-Abbas (hot, humid). The results revealed that annual efficiencies for solar collectors and PV panels reached up to 0.47 and 0.18, respectively. Yazd exhibited the highest solar energy potential with a peak radiation of 8311 kWh/m 2 , while Shahrekord demonstrated the most consistent thermal gain during spring and summer. The system successfully maintained the target pasteurization temperature (40 ± 5°C) with a solar fraction ranging from 0.036 to 0.32. These findings confirm that the integrated system reduces dependence on fossil fuel-based energy by increasing renewable energy contribution up to 32% (solar fraction) and also provides a promising sustainable solution for remote and energy constrained regions for milk pasteurization in diverse climatic conditions, enhancing both operational efficiency and environmental sustainability.